Reconstructing Three‐Dimensional Optical Anisotropy with Tomographic Müller‐Polarimetric Microscopy - Yang Chen; Arthur Baroni; Torne Tänzer; Leonard Nielsen; Marianne Liebi (Advanced Science)
Abstract Most visible light imaging methods using polarization to obtain ultrastructure information are limited to 2D analysis or require demanding phase measurements to be extended to 3D. A novel 3D polarized light imaging technique based on Müller‐matrix formulations is introduced which numerically reconstructs 3D optical birefringence, that is anisotropic refractive indices and optical axis orientation, in each volumetric unit of sample. The new method is demonstrated, tomographic Müller‐polarimetric microscopy, in simulation and using experimental data of 3D macroscopic sample of human trabecular bone sample, where the local main orientation of nanoscale collagen fibers is extracted with a resolution of ≈ 20 µm. Tomographic Müller‐polarimetric microscopy offers a low‐cost and experimentally simple imaging approach to access the ultrastructure which is not directly resolvable, in a wide range of biological and composite materials.